IDENTIFIKASI KARAKTERISTIK KAPASITANSI DAGING AYAM TIREN DAN DAGING AYAM NORMAL - Frida Agung Rakhmadi; Widayanti Widayanti; Anggara Wahyu Atmaja; Astika Rusma Dewi (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2013)
Identification of tiren chicken and normal chicken capacitance characteristic was done to know the characteristic of both of them based on their capacitance and to know whether the characteristic is different or same from both of them. The observed chicken components were chest, drumstick, tepong of broiler chicken. The measurement of capacitance was done using LCR meter, with adding the parallel plate apparatus. The result of research shown that the tiren chicken capacitance is higher than the normal chicken. The average capacitance of chest, drumstick, and tepong of tiren chicken are (2,20 ± 0,08) pF, (2,20 ± 0,09) pF, dan (2,00 ± 0,02) pF, while the average capacitance of chest, drumstick, and tepong of normal chicken are (1,10 ± 0,07) pF, (1,10 ± 0,08) pF, dan (1,10 ± 0,03) pF. Its differentiation was supported by t-test result.